Introduction: on resilience and solidarity. Issue 1 (2nd January 2017) - Vrasti, Wanda; Michelsen, Nicholas
Abstract: In this introduction to the special section on Resilience and Solidarity, Vrasti and Michelsen explore the ambiguous and mobile relationship between these concepts, drawing on resources from political theory, before setting out the challenges that arise out of our current and apparently post-political moment. They argue that thinking through the relationship between resilience and solidarity constitutes a space for interrogation into political possibilities under the contemporary condition. The introduction then reviews and charts how this line of thought runs through the four papers that make up the section.